Vasculitis mimics caused by Pythium infection and literatures review (Eng) - Norasetthada , Angkana (Thai Journal of Rheumatology, 2025)
While early diagnosis of vasculitis is important to induce remission and prevent organ damage, an incorrect diagnosis can result in harmful consequences from missing the underlying condition and exposure to immunosuppressive therapy. Evaluation of vasculitis should include consideration of its mimics. Important mimic categories include infection, vasculopathy, non-inflammatory conditions like atherosclerosis, thrombotic states, calciphylaxis and rare neoplasms.Human pythiosis is a rare life-threatening disease caused by Pythium insidiosum, a fungus-like organism that belongs to the Kingdom Straminiphila.Infected patients were mostly reported from Thailand and usually had an agricultural background. Clinical presentations are documented, cutaneous/subcutaneous, ocular, vascular, and disseminated pythiosis. The majority of the reported patients with vascular pythiosis have lower limb involvement.Known risk factors for vascular pythiosis include thalassemia, hemoglobinopathy, paroxysmal nocturnal hemoglobinuria, aplastic anemia, and leukemia. Furthermore, the rarity of the disease has led to underrecognition, under-diagnosis, and delays in diagnosis, and this has contributed to the occurrence of advanced disease, which affects survival. I, herein, report a case of diabetes mellitus and alcoholism, 31 year-old male presented with ischemic leg ulcers, which skin biopsy revealed leukocytoclastic vasculitis and CT- angiogram suspected vasculitis, and then P. insidiosum has been isolated from vascular sites, and relevant literature reviews.